Alarm fatigue and sleep quality in medical staff-a Polish-Czech-Slovak study on workplace ergonomics - Rypicz, Łukasz; Witczak, Izabela; Šupínová, Mária; Salehi, Hugh Pierre; Jarabicová, Oľga (Frontiers in public health, 2024)
BACKGROUND: Alarms are crucial in informing Healthcare Workers (HCWs) about critical patient needs, but unmanaged frequency and noise of alarms can de-sensitize medical staff and compromise patient safety. Alarm fatigue is identified as the major cause of the clinical alarm management problem. It occurs when the medical staff is overwhelmed by the number of clinical alarms. METHODS: The survey was conducted online using Google's form-making tools from June to July 2023. There were three parts to the survey used in the study: a socio-demographic metric, the Alarm Fatigue Assessment Questionnaire (AFAQ), and The Pittsburgh Sleep Quality Index (PSQI). A significance level of 0.05 was used in the analysis. RESULTS: The survey included 756 medical professionals from three European countries (Slovakia, the Czech Republic and Poland). The participants in the study were 42 years old on average, and they had 12 years of work experience. 603 out of 756 survey participants had poor sleep quality, 147 had good sleep quality, and 6 did not provide an answer. This study analyzed the alarm fatigue levels of respondents in every country. In the Czech Republic, Poland and Slovakia, a statistically significant association (p = 0.039, p = 0.001, p < 0.001) was found between alarm fatigue and sleep quality in medical staff. CONCLUSION: Based on our study, alarm fatigue and sleep quality of HCWs are correlated. Therefore, alarm fatigue and sleep hygiene should be monitored.
Keywords: dospělí; průzkumy a dotazníky; Female; Adult; Polsko; ženské pohlaví; únava; Surveys and Questionnaires; Ergonomics; klinické alarmy; pracoviště; lidé; Fatigue; Medical Staff; kvalita spánku; lékařský personál; ergonomie; Male; Czech Republic; Workplace; Česká republika; lidé středního věku; mužské pohlaví; Poland; Sleep Quality; Middle Aged; Clinical Alarms; Humans